1998
DOI: 10.1029/97jd02967
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent nucleation rate constants and freezing behavior of submicron nitric acid dihydrate aerosol particles under stratospheric conditions

Abstract: Abstract. The freezing of a submicron-sized aerosol composed of H20 and HNO 3 in a precise 2:1 concentration ratio has been measured using Fourier transform infrared extinction spectroscopy. The measurements were carried out in a flow tube operating at temperatures and pressures appropriate to the polar stratosphere. On the timescale of this measurement, about 15 s, detectable nucleation occurred at 179 _+ 1.6 K. Ten percent of the sample was frozen after 15 s at a temperature of 178.8 K; 50% was frozen at 177… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
94
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(106 citation statements)
references
References 33 publications
10
94
2
Order By: Relevance
“…The literature data sets also shown in Fig. 1 are taken from the nucleation rate measurements of (1) small droplets in an aerosol settling chamber (Disselkamp et al, 1996;Prenni et al, 1998) and an aerosol flow tube system (Bertram and Sloan, 1998a;Bertram et al, 2000), both with FITR detection for the transition from the liquid to the solid phase, and of (2) larger droplets deposited on cooled substrates with freezing detection by optical microscopy (Salcedo et al, 2000(Salcedo et al, , 2001 and Raman microscopy (Knopf et al, 2002). G act,v is plotted as function of the NAD saturation ratios, S NAD , which were, if not explicitly mentioned in the respective literature, calculated from the known composition of the nitric acid solutions and the temperature using the AIM thermodynamic model Clegg et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature data sets also shown in Fig. 1 are taken from the nucleation rate measurements of (1) small droplets in an aerosol settling chamber (Disselkamp et al, 1996;Prenni et al, 1998) and an aerosol flow tube system (Bertram and Sloan, 1998a;Bertram et al, 2000), both with FITR detection for the transition from the liquid to the solid phase, and of (2) larger droplets deposited on cooled substrates with freezing detection by optical microscopy (Salcedo et al, 2000(Salcedo et al, , 2001 and Raman microscopy (Knopf et al, 2002). G act,v is plotted as function of the NAD saturation ratios, S NAD , which were, if not explicitly mentioned in the respective literature, calculated from the known composition of the nitric acid solutions and the temperature using the AIM thermodynamic model Clegg et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…While recent field studies give direct evidence that NAT exists in PSCs (Voigt et al, 2000;Fahey et al, 2001;Brooks et al, 2003;Deshler et al, 2003;Voigt et al, 2005), laboratory investigations revealed the metastable NAD to nucleate in STS and binary water/nitric acid droplets at stratospheric temperatures (Disselkamp et al, 1996;Prenni et al, 1998;Bertram and Sloan, 1998a;Bertram et al, 2000;Salcedo et al, 2000Salcedo et al, , 2001Knopf et al, 2002;Stetzer et al, 2006). Tizek et al (2002) identified two metastable forms of the dihydrate, α-NAD and β-NAD, after annealing amorphous nitric acid samples of variable molar composition.…”
Section: Introductionmentioning
confidence: 99%
“…: 64 wt% HNO 3 (Bertram and Sloan, 1998a); : binary HNO 3 /H 2 O aerosol of varying composition (Bertram et al, 2000). (b) : 54 wt% HNO 3 (Salcedo et al, 2001); : 54 wt% HNO 3 (Bertram and Sloan, 1998b).…”
Section: Resultsmentioning
confidence: 99%
“…All data points were derived from experiments with droplets consisting of binary aqueous nitric acid solutions of varying composition. (a) : 57 wt%, 60 wt%, and 64 wt% HNO 3 (Salcedo et al, 2001); : 64 wt% HNO 3 (Bertram and Sloan, 1998a). (b) : 54 wt% HNO 3 (Salcedo et al, 2001); : 54 wt% HNO 3 (Bertram and Sloan, 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…Using Powell's multidimensional optimisation method (Press et al, 1988(Press et al, , 1992, the aerosol number density N as well as the count median diameter CMD and the mode width σ g of the log-normal size distribution were retrieved by minimising the summed squared residuals between experimental and calculated spectra. As discussed in numerous publications (Bertram and Sloan, 1998;Disselkamp et al, 1996;Echle et al, 1998;Eldering et al, 2001), the fit becomes insensitive to the parameters CMD and σ g when the particle radii are small compared to the wavelength of the incident radiation, i.e. approach the Rayleigh limit of Mie theory.…”
Section: Ftir Measurements and Retrieval Of Aerosol Parametersmentioning
confidence: 96%